Development of a Digital Storybook Based on Lebak Culture to Foster Critical Thinking Skills in Early Childhood - Rohita, Rohita; Erika Firmiana, Masni; Arianti, Gusmia (JURNAL PENDIDIKAN USIA DINI, 2025)
Critical thinking is a vital 21st-century skill that should be nurtured from an early age. One effective approach is through the use of digital storybooks based on local culture. Despite its rich cultural heritage, including the traditions of the Baduy people, integration of local culture into early childhood education in Lebak Regency remains limited. A survey of 40 kindergarten teachers found that only 7 schools had access to reading materials related to Lebak’s local culture. This study aimed to develop a digital storybook titled “Hitam Putih Pakaian Adat Suku Baduy” using the ADDIE model. Validation results from media experts (95%), early childhood education experts (83%), communication experts (93%), and prospective users (91%) indicated that the product was highly feasible. Field trials with 10 children aged 5–6 years showed that the most developed critical thinking skills were evaluation and self-regulation, with average scores across six aspects ranging from 2.6 to 3.8 on a 4-point scale. Interpretation and inference were also strong, while analysis and explanation required additional support. These findings suggest that culturally based digital storybooks can effectively foster critical thinking in early learners, but teacher involvement remains essential to enhance deeper reasoning and understanding.